C4 rice: a challenge for plant phenomics - Furbank, Robert T.; von Caemmerer, Susanne; Sheehy, John; Edwards, Gerry (Commonwealth Scientific and Industrial Research Organisation, 2009)
There is now strong evidence that yield potential in rice (Oryza sativa L.) is becoming limited by ‘source’ capacity, i.e. photosynthetic capacity or efficiency, and hence the ability to fill the large number of grain ‘sinks’ produced in modern varieties. One solution to this problem is to introduce a more efficient, higher capacity photosynthetic mechanism to rice, the C4 pathway. A major challenge is identifying and engineering the genes necessary to install C4 photosynthesis in rice. Recently, an international research consortium was established to achieve this aim. Central to the aims of this project is phenotyping large populations of rice and sorghum (Sorghum bicolor L.) mutants for ‘C4-ness’ to identify C3 plants that have acquired C4 characteristics or revertant C4 plants that have lost them. This paper describes a variety of plant phenomics approaches to identify these plants and the genes responsible, based on our detailed physiological knowledge of C4 photosynthesis. Strategies to asses the physiological effects of the installation of components of the C4 pathway in rice are also presented.